2008
DOI: 10.1016/j.jsb.2008.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Native cellular architecture of Treponema denticola revealed by cryo-electron tomography

Abstract: Using cryo-electron tomography, we are developing a refined description of native cellular structures in the pathogenic spirochete Treponema denticola. Tightly organized bundles of periplasmic flagella were readily observed in intact plunge-frozen cells. The periplasmic space was measured in both wild-type and aflagellate strains, and found to widen by less than the diameter of flagella when the latter are present. This suggests that a structural change occurs in the peptidoglycan layer to accommodate the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
48
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 52 publications
9
48
0
Order By: Relevance
“…4). The outer surfaces of the basal bodies (i.e., those parts of the basal bodies that directly face the periplasmic space), with the hook region exposed, were approximately 38 nm in diameter, which is similar to those reported for T. primitia (35 nm) but somewhat greater than those of T. denticola (29 nm) (21,33). Each basal body appeared as a ring, with a dense region in the center.…”
Section: Overall Cell Morphologysupporting
confidence: 73%
See 1 more Smart Citation
“…4). The outer surfaces of the basal bodies (i.e., those parts of the basal bodies that directly face the periplasmic space), with the hook region exposed, were approximately 38 nm in diameter, which is similar to those reported for T. primitia (35 nm) but somewhat greater than those of T. denticola (29 nm) (21,33). Each basal body appeared as a ring, with a dense region in the center.…”
Section: Overall Cell Morphologysupporting
confidence: 73%
“…For example, electron microscopy of hydrated sections of E. coli and Pseudomonas aeruginosa indicated that the periplasmic space is markedly thinner than indicated by results previously obtained using fixed cells (28). Here we analyzed the structure of B. burgdorferi using electron cryotomography and compared our results to those recently reported for Treponema primitia and Treponema denticola (21,34). We found not only that is its periplasmic space quite thin but that the periplasmic flagella do not form a bundle as previously thought (18,31).…”
supporting
confidence: 49%
“…However, we were surprised that 26.4% (versus only 1.7% in the wild type) ( Table 2) of the motors/periplasmic flagella were oriented toward the cell pole rather than extending toward the middle of the cell body. This remarkable phenotype has not been observed for previously characterized spirochetal flagellar mutants (24,41). FliL is therefore likely to play a role in defining the orientation of periplasmic flagella in B. burgdorferi (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Recently, cryo-electron tomography (cryo-ET) was utilized to determine the molecular architecture of the spirochete flagellar motor in situ (24,25,40,41). These studies suggested that the overall spirochetal flagellar motor structures (the MS ring, the C ring, and the export apparatus) are similar to those of other bacteria, e.g., E. coli (9,25,31,33,40,41,47).…”
mentioning
confidence: 99%
“…This technique involves collecting a tilt series of images from different angles at high magnification and computationally reconstructing a 3-D density map of the intact organism. Recently, cryo-ET has been extensively utilized to study many spirochetes (1,7,14,15,19,28,32,33), particularly, in our hands, to study the intact flagellar motor structure of B. burgdorferi (25) as well as the cell envelope architecture of T. pallidum (24).…”
mentioning
confidence: 99%